Noise Monitoring Study at Universiti Malaysia Kelantan Campus - Ghani, Nurfazila (2016)
This study is about monitoring the noise level at UMK Campuses. The purpose of this study is to determine whether the noise level at UMK Campuses follow the standard noise level that been provided in guidelines by Department of Environment Malaysia. Noise pollution is an unwanted sound that could give negative effects to human behaviors especially in sensitive area such as educational area. Universiti Malaysia Kelantan has three campuses which are in Pengkalan Chepa, Bachok and Jeli. Each campus has one site selected for noise level monitoring. These selected sites were selected due to hotspot area. The noise level was determined by calculating the average of the A- weighing, dB(A) which was obtained from the data sampling. The data were recorded for day and night to obtain the continuous of instantaneous sound pressure level. The equipment that been used in this study is TM-102 Sound Level Meter Auto Ranging for measure the noise level for each campus. The average of noise level recorded for each campus were compared with maximum permissible sound Level for development by the Department of Environment. Since Pengk:alan Chepa, Jeli and Bachok are categorized as urban areas, the average of noise level recorded were compared with level 60 dB for day time and 50 dB for night time. The higher noise level recorded for each campus during the first week of November during day time was 61.22 dB at UMK Jeli, 65.96 dB at UMK Pengkalan Chepa and 56.62 dB at UMK Bachok. While at night time, the highest level of noise level recorded was 53.04 dB at UMK Jeli, 64.86 dB at UMK Pengk:alan Chepa and 53.68 dB at UMK Bachok. The higher noise level recorded for each campus during the second week of November during day time was 55.18 dB at UMK Jeli, 61.02 dB at UMK Pengk:alan Chepa and 55.52 dB at UMK Bachok. While at night time, the highest level of noise level recorded was 52.68 dB at UMK Jeli, 51.68 dB at UMK Pengk:alanChepa and 50.16 dB at UMK Bachok. The higher noise level recorded for each campus during the third week of November during day time was 59.98 dB at UMK Jeli, 67.48 dB at UMK Pengk:alan Chepa and 55.18 dB at UMK Bachok. While at night time, the highest level of noise level recorded was 52.40 dB at UMK Jeli, 64.22 dB at UMK Pengk:alan Chepa and 51.68 dB at UMK Bachok.